Gold mining, discourses, and threats: What is really damaging the fluvial hydrosystem of the Faleme River? - EL HADJI SERIGNE TOP; Géraud Magrin; Gilles ARNAUD-FASSETTA; Mouhamadou Lamine DIALLO (Journal of Political Ecology)
The gold rush in the Faleme catchment between Senegal and Mali involves artisanal miners from the sub-region, European and American multinationals, and medium-sized Chinese companies. These miners, with their disproportionate financial and material resources, practise three types of gold mining (artisanal, industrial and semi-industrial) involving the Faleme River. The mining techniques used by these operators are now a major source of damage to the river. This damage is mainly water pollution, the destruction of riverbanks, and the disappearance of aquatic fauna and agro-pastoral activities. The level of degradation is a source of speculation. Attempts are made to emphasize that artisanal exploitation is the main activity degrading the river. This article deconstructs these arguments with evidence showing that, in addition to artisanal gold mining, industrial and semi-mechanical mining activities are major contributors to the degradation of this river.